Growth of Ophioderma cinereum (Müller & Troschel, 1842) (Echinodermata: Ophiuroidea) in two rock shores of the Salvador City, Bahia, Brazil - Tanure, Bruna Marques; Cerqueira, Walter Ramos Pinto (SITIENTIBUS série Ciências Biológicas, 2007)
Ophioderma cinereum is a very common ophiuroid that can be found on the beaches of the seaside of Salvador City, on the northern coastline of Bahia State, and in the Todos os Santos Bay. However, there is a lot to learn about aspects of the life of these species, mainly about those aspects related to their secondary production and growth. This paper aims at learning more about the aspects related to the biomass and growth of O. cinereum that inhabit the beaches of Pituba and Itapuã, Salvador. Collection of specimens was done every two months, from June 2005 to June 2006 at periods of low tide. The animals were placed in sea water and anesthetized with crystals of magnesium chloride; after, they were treated with formaldehyde 4%, and preserved in alcohol 70%. In the laboratory, the specimens were put in tissue paper to dry during three minutes and weighed on analytic scale, to measure its total wet weight. They were dismembered from the disc next to the base and the members were individually measured in weight, length and height. The diameter and height of the discs were also individually measured. A spreadsheet was used to compare and analyze measured data and to calculate related media and other statistics analyzes. The diameter of the disc was considered the best variable to analyze the growth of the specimens, because it does not depend on the height of the disc. During the search, it was not identified any case of recruitment, with introduction of any young specimen in the two searched populations, which can be a signal of division of habitat, and different ecological niche for the young and for the adult specimen of O. cinereum. In general, it was observed different dynamics for the O.cinereum from two beaches in the work, and those dynamics reflected the influence of the particular conditions of each environment.